Determination of Subclinical Mastitis Prevalence in Dairy Cows in Turkiye through Meta-Analysis and Production Loss Calculation - Arikan, Mehmet Saltuk; Mat, Burak; Alkan, Hasan; Cevrimli, Mustafa Bahadir; Akin, Ahmet Cumhur; Basar, Ebru Kaya; Tekindal, Mustafa Agah (Univ Agriculture, Fac Veterinary Science, 2024)
In recent years, many studies have been conducted on mastitis, and preventive measures have been taken to curb it. However, mastitis continues to cause great economic losses in dairy farms and negatively affects high-yielding dairy cows. The current study aims to consolidate the prevalence of subclinical mastitis among dairy cows in Turkiye and to estimate economic losses due to mastitis. The random-effects model (Sidik-Jonkman Knapp and Hartung method) was used for the meta-analysis to determine between-study and within-study variances. Economic losses due to subclinical mastitis were calculated on the prevalence value calculated by meta-analysis. Analyses revealed a high heterogeneity between studies based on cows (Q = 1,590.86, df = 25, p < 0.01, I-2 = 98.21) and udder lobes (Q = 732,802, df = 21, p < 0.001, I-2 = 97.83). The pooled estimate of subclinical mastitis prevalence in 10,334 cows from 26 studies was 44.13% (95% confidence interval [CI]: 36.00-52.50). A meta-analysis consisting of 21,745 udder lobes from 22 studies revealed the prevalence of udder lobe-based subclinical mastitis to be 31.44% (95% CI: 27.00-36.20). The meta-analysis yielded statistically high heterogeneity for prevalence estimates in published studies. The economic analysis revealed an economic loss of 1,095.88, 3,221.26, and 8,455.91 TL (equivalent to 233.17, 685.37, and 1,799.13 L of milk, 84.3, 247.8 and 650.5 USD$) per animal in mild, moderate, and severe cases, respectively. In this study, Meta-analysis in T & uuml;rkiye reveals varying subclinical mastitis prevalence, addressing inconsistencies across studies. These economic loss calculations provide producers, policymakers, and other stakeholders in the industry with the scientific information necessary to develop effective strategies to combat subclinical mastitis.
Keywords: Meta -analysis; Prevalence; Subclinical; Mastitis; Cost-analysis